1990
DOI: 10.1002/eji.1830200417
|View full text |Cite
|
Sign up to set email alerts
|

Selective expansion of a specific anti‐tumor CD8+ cytotoxic T lymphocyte clone in the bulk culture of tumor‐infiltrating lymphocytes from a melanoma patient: Cytotoxic activity and T cell receptor gene rearrangements

Abstract: In vitro culture of metastatic melanoma fragments with 150 units of recombinant interleukin 2 resulted in the successive expansion of CD4+ and then CD8+ tumor-infiltrating lymphocytes (TIL) throughout a 2-month period. TIL cultured for 43 days and consisting of 95% CD8+ and 10% CD4+ T lymphocytes were cloned by limiting dilution (LD). Thirteen CD8+ and thirty-one CD4+ clones were obtained, indicating that the frequency of clonogenic CD8+ proliferative T lymphocytes was much lower than that of their CD4+ homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 30 publications
4
36
0
1
Order By: Relevance
“…Metastatic melanoma cell lines were established from tumorinvaded lymph node fragments as described previously (Gervois et al, 1990;Dreno et al, 2002;Labarriere et al, 2002). Melanoma cell lines were established before injection of autologous TILs plus IL-2 or IL-2 only.…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…Metastatic melanoma cell lines were established from tumorinvaded lymph node fragments as described previously (Gervois et al, 1990;Dreno et al, 2002;Labarriere et al, 2002). Melanoma cell lines were established before injection of autologous TILs plus IL-2 or IL-2 only.…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…In malignant melanoma, it has been shown that TIL are able to recognize tumour-associated antigens, and in some cases to lyse the malignant cells [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. These findings provided a basis for the use of in vitro cultured TIL in adoptive immunotherapy in an effort to enhance the in vivo accumulation of tumour-lytic lymphocytes [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…Blocking experiments using MoAb recognizing the CD3 antigen or the a/^TCR inhibited cytotoxicity at the effector cell level, demonstrating that these cell surface structures were involved in the cytolytic process. Southern blotting analysis revealed an oligoclonal pattern of /3-chain TCR gene rearrangements on melanoma [7,32] or ovarian carcinoma [26] TIL T cell lines with aulologous tumour-specific cytotoxicity. Culture of mixtures of melanoma or ovarian carcinoma TIL and tumour cells in low [5,7] or high [6,29 31] concentrations of rIL-2 resulted in rapid expansion of the T cells up to 3500-fold or higher, without the need for a single restimulation with autologous tumour celts [7].…”
Section: Discussionmentioning
confidence: 99%